Analysis of vibration and sound insulation characteristics of functionally graded sandwich plates. (1st October 2020) - Chen, Yu-xin; Li, Feng-lian; Hao, Yu-xin
Abstract: Based on the first-order shear deformation theory, free vibration and sound insulation of functionally graded material (FGM) sandwich plates with four simply supported edges are studied and analyzed. The sandwich plate with FGM face sheets and homogeneous core and the sandwich plate with FGM core and homogeneous face sheets are considered. Using Navier method and fluid–solid coupling conditions, the vibration and coupled vibro-acoustic dynamic equations for FGM sandwich plates with simply supported edges are established and solved numerically. The natural frequencies and the sound insulation of FGM sandwich plates obtained theoretically are compared with the numerical simulation results. It is shown that the theoretical model of the vibration and the coupling vibro-acoustic theoretical model for the FGM sandwich plate are accurate and feasible. On this basis, the sound insulation characteristics of two types of FGM sandwich plates are analyzed, and the effects of parameter changes (incident angles, gradient index, core thickness, Poisson's ratio) on the fundamental frequency and sound insulation are discussed.